Teoria das Molduras Relacionais (RFT): uma revisão de estudos empíricos - Boavista, Rodrigo Rodrigues Costa (2014)
Relational Frame Theory (RFT) was proposed by Steven Hayes and Aaron Brownstein in 1985. Only in 2001 the first book whose content was exclusively dedicated to present RFT proposal and application fields was released. Inspired by research on stimulus equivalence and operant understanding of language RFT proponents argue that verbal behavior is closely related to a high order operant strengthened since early childhood via multiple exemplars training. This operant - arbitrarily applicable relational responding is defined by the properties of mutual implication, combinatorial implication, and transformation of stimuli function. RFT has received criticism directed to iits philosophical foundations, theoretical assumptions and regarding methodological research practices that guarantee its empirical support. This study aimed to review the empirical literature produced in the light of the RFT analyzing bibliometric aspects (year of publication, authors, affiliation of authors, journals, journals´ relevancy rates), methodological aspects (participants´ age, diagnosis and education, type and site of application, material and equipment used, relational frame employed, experimental task and measurement used) and trials to comprehend phenomena traditionally explore by other areas of knowledge/research lines/theories. 85 articles published between 1991 and May 2013 were reviewed. The Psychological Record led publications (42 articles). Studies majority employed participants from 18 years old onwards. Only 8% considered participants with psychiatric diagnosis. Just one publication was conducted in a group setting. Great part of the studies used computerized tasks. In terms of relational frames 68 studies investigated coordinated relations. 53 publications employed simultaneous matching-to-sample procedure. Between 1991 and 2001 there were nine studies that combined at least two measures but between 2006 and May 2013 there were 35. We found articles in which phenomena traditionally explored by areas such as philosophy, heuristic, clinics, theory of mind, neuroscience, among others, were discussed. Results show that RFT researchers produced empirical data through a variety of methodological conditions. However, we didn´t find evidence on non-human subjects or studies which assessed results in terms of sociodemographic variables or number of training and testing trials